The contribution of community pharmacy to improving the public’s health. Report 3, An overview of evidence-base from 1990-2002 and recommendations for action - Armstrong, Miriam; Lewis, Ruth; Anderson, Claire; Blenkinsopp, Alison (PharmacyHealthLink and the Royal Pharmaceutical Society of Great Britain, 2005)
Community pharmacists have always played a significant role in promoting, maintaining and improving the public’s health. Based at the heart of communities, they gain a unique understanding of the health needs of the communities they serve through daily interactions with patients and customers. Reports 1 and 2 of the Evidence Base Review clearly demonstrate the potential for community pharmacists to improve the public’s health. There has been increasing recognition of the contribution that they can make to improving the public’s health and the need to integrate them into the wider public health workforce. The new pharmacy global contracts and pharmacy public health strategy for England sets the framework for the current and future public health role of pharmacy. We hope this role will develop further and that community pharmacists’ skills and knowledge will be harnessed even more effectively in order to improve the public’s health. The following report summarises the evidence base linked to national targets and makes recommendations for action. PCTs may wish to use the findings to develop pharmacy services to improve the health of communities that they serve and to meet local health improvement targets.